Macular pigment levels following successful macular hole surgery. Issue 9 (19th August 2005) - Neelam, K; O'Gorman, N; Nolan, J; O'Donovan, O; Eong, K G Au; Beatty, S
Abstract : Aim: Macular pigment (MP) is composed of two hydroxycarotenoids contained within the photoreceptors and the axons of the central neurosensory retina, with peak concentrations in the Henle layer. A full thickness macular hole (FTMH) is characterised by absence of all retinal layers in an area centred at the former centre of the fovea. The authors report the results of a study designed to investigate MP levels in patients following successful FTMH surgery, using Raman spectroscopy, and to correlate these findings with functional and topographic outcomes. Methods: The following details were recorded for 12 eyes of 12 patients following successful closure of a FTMH: best corrected visual acuity; macula threshold test, fixation, fundus photography, and macular pigment levels using Raman spectroscopy. High resolution imaging of the retina using optical coherence tomography (OCT) was performed in nine of the 12 study eyes. Results: Mean (SD) best corrected visual acuity was 0.6 (0.4) and improved significantly from preoperative levels. On macula threshold testing of the operated eye, a central scotoma was detectable in one eye only (8.3%). MP levels were demonstrable in 10 of the 12 study eyes following successful FTMH surgery. MP levels were higher in three study eyes, and lower in seven study eyes, when compared with the fellow eye. Of the three pairs of eyes where MP levels were greater in the study eye, macular pathology was present in two fellow eyes. Conclusions: The presence of MP was confirmed in the neurosensory retina of an anatomically closed FTMH in 10 of 12 study eyes, although the levels were lower than the fellow normal macula in nine of 10 cases. This suggests a good degree of physiological recovery of photoreceptors and their axons following successful FTMH surgery.